The Impact of Expanding Simplified Start-up Procedures to More Remote Areas : The Minas Facil Expresso Program - Bruhn, Miriam; McKenzie, David (World Bank, Washington, DC, 2014)
This note shows how the rich administrative data collected by many governments can be used to evaluate a policy reform, and provides an example where impact evaluation reveals that a policy didn t work as well as intended.